(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores the importance of visual images in bioinformatics processes and discusses the role of information technology in their development. It explores the importance of visualization tools for understanding complex biological data, reviews the existing literature, and presents a methodology for creating effective visualizations. Experiments and results are presented to demonstrate the practical application of these visualizations, highlighting their potential to advance bioinformatics research and applications.